Estrutura eletrônica em sistemas moleculares de interesse espacial e atmosférico. - Coura, Daniel Vitor Barbosa (2023)
In this work, electronic structure calculations of high theoretical level were made through multiconfigurational methods aiming at three objectives: the first, to propose a new extrapolation method of the dynamic correlation energies to the Complete Basis Set (CBS) - limit, where a good agreement with results available in the bibliography is obtained, even when the (d, t) pair of hierarchical numbers is used to perform the extrapolation; the second objective is to fit ab initio extrapolated points to the CBS limit via the unified singlet- and triplet-pair method of the molecular system HN2 to an analytic function using the double many-body expansion method for the quartet state, being the first potential energy surface constructed for this state, allowing, for the first time, the prediction of the role played by the quartet state in N(4S) + NHN(4S) + NH(˜X³Σ¯) collisions; and the third, to build a potential energy surface using the extrapolation method developed here for the molecular system HCO, this work is in progress and a preliminary fit is shown.